2009
DOI: 10.5194/angeo-27-2523-2009
|View full text |Cite
|
Sign up to set email alerts
|

Tropical cyclone genesis in the Southern Hemisphere and its relationship with the ENSO

Abstract: Abstract. Tropical cyclogenesis climatology over the South Indian and South Pacific Oceans has been developed using a new tropical cyclone (TC) archive for the Southern Hemisphere, and changes in geographical distribution of areas favourable for TC genesis related to changes in the El Niño-Southern Oscillation (ENSO) phases have been investigated. To explain these changes, large-scale environmental variables which influence TC genesis and development such as sea surface temperatures (SSTs), relative humidity i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
63
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(71 citation statements)
references
References 23 publications
6
63
1
1
Order By: Relevance
“…The number of landfalling TCs has declined since the late 1800s (Callaghan and Power, 2011); the cause of this remains unclear. El Niño (La Niña) is associated with an eastward (westward) shift in tropical cyclogenesis regions in the Southwest Pacific, reducing (increasing) the number of landfalling TCs in eastern Australia (Hastings, 1990;Kuleshov et al, 2009). Callaghan and Power (2011) demonstrated that all years with multiple TC landfalls were La Niña years, while Walsh and Syktus (2003) concluded that near the Queensland coast strong La Niña conditions were associated with five times as many TC days as strong El Niño conditions.…”
Section: Drivers Of Inter-annual and Decadal Rainfall Variabilitymentioning
confidence: 99%
“…The number of landfalling TCs has declined since the late 1800s (Callaghan and Power, 2011); the cause of this remains unclear. El Niño (La Niña) is associated with an eastward (westward) shift in tropical cyclogenesis regions in the Southwest Pacific, reducing (increasing) the number of landfalling TCs in eastern Australia (Hastings, 1990;Kuleshov et al, 2009). Callaghan and Power (2011) demonstrated that all years with multiple TC landfalls were La Niña years, while Walsh and Syktus (2003) concluded that near the Queensland coast strong La Niña conditions were associated with five times as many TC days as strong El Niño conditions.…”
Section: Drivers Of Inter-annual and Decadal Rainfall Variabilitymentioning
confidence: 99%
“…Here the SOI index is also anti-correlated with temperature, which is in agreement with most results published in the literature. As discussed by Kuleshov et al (2009), ENSO induces anomalous circulation in the Indian region. ENSO affects the intensity of the easterly winds as well as the SST and the relative humidity in the middle troposphere and thus changes Walker circulation.…”
Section: Correlation Analysis: Enso Iod Qbo Ssnmentioning
confidence: 99%
“…A number of environmental factors critical for SIO cyclone development has been identified. For example, Kuleshov et al (2009a) attribute shifts in cyclone tracks during ENSO phases to changes in vorticity and relative humidity and Camargo et al (2007) showed that the track shifts are primarily due to changes in vertical wind shear.…”
Section: Large-scale Environmental Variables Which Influence Tropicalmentioning
confidence: 99%
“…Analysing geographical variation in TC activity in the SPO, Basher and Zheng (1995) and Kuleshov et al (2009a) have demonstrated that cyclones tend to form in the southwest of the basin in La Niña years compared with El Niño years. A plausible explanation for this eastwest shift is change in distribution of the sea surface temperatures over the Pacific during El Niño and La Niña.…”
Section: Large-scale Environmental Variables Which Influence Tropicalmentioning
confidence: 99%